To multiply these polynomials together you multiply each term from the first polynomial with each term from the second. I will show you this below:

s^2 * 5s = 5s^3 because the coefficients of 1 * 5 = 5 and when multiplying factors (s in this case) you add their powers 2 + 1 = 3 so s would be to the 3rd power.

s^2 * 2 = 2s^2

6s * 5s = 30s^2

6s * 2 = 12 s

-5 * 5s = -25s

-5 * 2 = -10

Then you can put them all in one polynomial and add like terms that have the same factor to a certain power (I will bold one set and underline another for you)

5s^3 + 2s^2 + 30s^2 + 12s + (-25s) + (-10)

The simplified solution is:

5s^3 + 32s^s - 13s - 10

Please let me know if you have any questions, I hope that I helped!